1995
DOI: 10.1021/j100017a037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of "Inert" Counterions on the Photochemistry of Some Cationic Polymethine Dyes

Abstract: The effects of "inert" counterions on some photochemical processes involving cationic polymethine dyes have been studied in ion pairs formed in low-polar media. In particular, the counterion effects on the back isomerization kinetics of photoisomers of benzimidacyanine and indotricarbocyanine dyes and on the triplet state decay of the benzimidacyanine dyes have been investigated by flash photolysis. The increase in the rate constant and decrease in the activation energy of back isomerization of benzimidacyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…We acquired high-performance liquid chromatography (HPLC) of the TTBC iodide to eliminate the impurity quenching and found that the sample was 99.90% pure. Tatikolov et al reported that the interaction between a benzimidazolocarbocyanine cation and iodide counterion forms an ion-pair in low polar medium and leads to enhancement of the internal conversion rate [45]. However, the ion-pair formation in methanol is not expected.…”
Section: Resultsmentioning
confidence: 99%
“…We acquired high-performance liquid chromatography (HPLC) of the TTBC iodide to eliminate the impurity quenching and found that the sample was 99.90% pure. Tatikolov et al reported that the interaction between a benzimidazolocarbocyanine cation and iodide counterion forms an ion-pair in low polar medium and leads to enhancement of the internal conversion rate [45]. However, the ion-pair formation in methanol is not expected.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence quantum yield and the fluorescence lifetime of the polymethine dye molecules decrease symbatically with strengthening of the anion-cation interactions [2, 3]. In the ion pairs, the probabilities of torsional vibrations in the polymethine chain are higher and the yield for photoisomerization of the molecules is higher; the degree of vibronic interactions and the probabilities of rotation about bonds are higher as more stable ion pairs are formed [4][5][6].Despite the significant number of publications devoted to study of the photophysical properties of polymethine dyes in different types of solvents, due attention has not been paid to the effect of the state of ionic equilibria on the efficiency of singlet oxygen generation by polymethine dyes. At the same time, such a study is important from both a scientific and an applied viewpoint.…”
mentioning
confidence: 99%
“…The fluorescence quantum yield and the fluorescence lifetime of the polymethine dye molecules decrease symbatically with strengthening of the anion-cation interactions [2, 3]. In the ion pairs, the probabilities of torsional vibrations in the polymethine chain are higher and the yield for photoisomerization of the molecules is higher; the degree of vibronic interactions and the probabilities of rotation about bonds are higher as more stable ion pairs are formed [4][5][6].…”
mentioning
confidence: 99%
“…Based on the data given in [1,11], an absorption spectrum of contact ion pairs is shifted to the short-wavelength region as compared to the spectrum for free ions of the dye and solvent-separated ion pairs. Attribution of short-wavelengths centers of the compounds under study to contact ion pairs is associated with their lower quantum efficiency of fluorescence, as for molecules in the state of contact ion pairs the probabilities of photoisomerization and torsional vibrations of the polymethine chain are higher [4][5][6]. The centers with longer-wavelength bands in absorption, fluorescence, and fluorescence excitation spectra are due to free ions in the solution.…”
Section: Discussionmentioning
confidence: 99%
“…The ionic pairs reveal higher probabilities of torsional vibrations in a polymethine chain and higher efficiency of the molecular photoisomerization. A degree of vibronic interactions and probability of rotation about the bonds is the higher the stronger ionic pairs are formed [4][5][6].…”
Section: Introductionmentioning
confidence: 99%